ESR1 Gene Mutation in Hormone Receptor-Positive HER2-Negative Metastatic Breast Cancer Patients: Concordance Between Tumor Tissue and Circulating Tumor DNA Analysis - Urso, Loredana; Vernaci, Grazia; Carlet, Jessica; Lo Mele, Marcello; Fassan, Matteo; Zulato, Elisabetta; Faggioni, Giovanni; Menichetti, Alice; Di Liso, Elisabetta; Griguolo, Gaia; Falci, Cristina; Conte, Pierfranco; et al. (Frontiers in Oncology, 2021)
Endocrine therapy represents the cornerstone of treatment in hormone receptor-positive (HR+), HER2-negative metastatic breast cancer (mBC). The natural course of this disease is marked by endocrine resistance, mainly due to Estrogen Receptor 1 (ESR1) acquired mutations. The aim of this study is to evaluate the concordance between ESR1 status in metastatic tumor specimens and matched circulating tumor DNA (ctDNA). Forty-three patients with HR+, HER2-negative mBC underwent both a metastatic tumor biopsy and a liquid biopsy at the time of disease progression. DNA extracted from formalin fixed paraffin embedded (FFPE) tumor specimens and ctDNA from matched plasma were analyzed by droplet digital (dd)PCR for the main ESR1 mutations (Y537S, Y537C, Y537N, D538G, E380Q). We observed a total mutation rate of 21%. We found 6 mutations on tissue biopsy: Y537S (1), D538G (2), Y537N (1), E380Q (2). Three patients with no mutations in tumor tissue had mutations detected in ctDNA. The total concordance rate between ESR1 status on tumor tissue and plasma was 88%. Our results confirm the potential role of liquid biopsy as a non-invasive alternative to tissue biopsy for ESR1 mutation assessment in mBC patients.